Rotation nozzle and numerical simulation of mass distribution at corners in 3D cementitious material printing - Liu, Zhixin (2021)
When conducting corner printing with rotational rectangular nozzle, a greater amount of material is deposited inside the filament and hence tearing and skewing will occur on the surface of the printed filament. With the aim of maintaining the surface finish and mechanical properties of the printed filament, a 3D numerical model is developed to study the flow mechanism at a corner under various conditions during the extrusion and deposition processes with rotational nozzle. After experimental validation, the numerical model is employed to study the material flow mechanism under various conditions. The results indicate that the rheological properties have little effect on the mass distribution ratio. However, a high relative nozzle travel speed, larger corner radii and lower nozzle aspect ratio is a promising route in obtaining a uniform material distribution ratio. The interlinking of process parameters affects the material distribution ratio significantly as well. Furthermore, the importance of the factors that affect the mass distribution was determined quantitatively.